Coadjoint Orbits of Lie Algebras and Cartan Class - Goze, M.; Remm, E. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
We study the coadjoint orbits of a Lie algebra in terms of Cartan class. In fact, the tangent space to a coadjoint orbit O(α) at the point α corresponds to the characteristic space associated with the left invariant form α, and its dimension is the even part of the Cartan class of α. We apply this remark to determine Lie algebras such that all the nontrivial orbits (nonreduced to a point) have the same dimension, in particular when this dimension is 2 or 4. We also determine the Lie algebras of dimension 2n or 2n+1 having an orbit of dimension 2n.